2015
DOI: 10.1038/ncomms7578
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductance of metal–diamond interfaces at high pressure

Abstract: The thermal conductance of interfaces between metals and diamond, which has a comparatively high Debye temperature, is often greater than can be accounted for by twophonon processes. The high pressures achievable in a diamond anvil cell (DAC) can significantly extend the metal phonon density of states to higher frequencies, and can also suppress extrinsic effects by greatly stiffening interface bonding. Here we report time-domain thermoreflectance measurements of metal-diamond interface thermal conductance up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 57 publications
12
119
0
Order By: Relevance
“…Anharmonic or three-phonon scattering processes typically become important at room temperature and above, in which a phonon of energy ω incident on the interface could transmit or reflect multiple phonons with appropriate energies to ensure energy conservation. This mechanism has been postulated to be important in acoustically mismatched interfaces such as Pb-diamond 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Anharmonic or three-phonon scattering processes typically become important at room temperature and above, in which a phonon of energy ω incident on the interface could transmit or reflect multiple phonons with appropriate energies to ensure energy conservation. This mechanism has been postulated to be important in acoustically mismatched interfaces such as Pb-diamond 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, G across metal-dielectric interfaces have been extensively measured [4][5][6][7][8][9] and modeled [10][11][12][13][14], but a systematic study of metal alloy composition's influence on G has not been considered.…”
mentioning
confidence: 99%
“…Sadasivam et al 55 performed first-principles calculations of electron-phonon coupling near a C49 TiSi 2 -Si interface and found that the coupling of electrons with joint or interfacial phonon modes can potentially produce a conductance similar to the phonon-phonon interfacial conductance (note: in the present paper, we obtained the C54 phase of TiSi 2 which is the lower resistivity phase and is more commonly used for semiconductor applications). Inelastic phonon scattering has been identified as an important transport mechanism for material combinations with a large acoustic mismatch such as Pb and diamond 56,57 . In the case of CoSi 2 of Si(111), we show in a forthcoming publication that the high temperature behavior of interface conductance can be matched quite well by invoking these mechanisms 54 .…”
Section: A Thermal Interface Conductance Of Epitaxial and Non-epitaxmentioning
confidence: 99%